The relationships of language proficiency, perceptions of writing in English language and writing experiences to the composing processes of 22 Filipino ESL writers : a case study of ESL composing - Reynales, Macralita Jose (Animo Repository, 1991)
This study investigates the composing processes/behaviors of 22 Filipino basic student writers enrolled in English for academic study at the Polytechnic University of the Philippines in relation to their language proficiency, perceptions of writing in English language, and writing experiences.The study made use of descriptive-normative and case analytical approaches mainly utilizing protocol analysis. Through the protocol analysis, identification and description of the various composing dimensions or behaviors--including time spent and rate of composing--were arrived at. In addition, observations and in depth structured interviews were employed. Seven kinds of data were analyzed in this study were scores on ESL Composition Tests, scores on NCEE and PUPCET Verbal Ability Tests, responses to questionnaires, responses to the interview on writing perceptions and writing experiences taken from the tapes, student-written product or drafts 6) student think-aloud protocols, and responses to the post composing interview questions.The findings of the study drew the following conclusions: 1) The very brief span of time the subjects spent for total composing and pre-writing might suggest the students' lack of commitment to the writing 2) Planning is either mental or verbal 3) The subjects did not exert considerable efforts to produce satisfactory essays and did not have a full understanding of what elements constituted good writing 4) The occurrences of reading, rescanning and rereading, though few, served the subjects as breathing space for revisions and for creating, organizing and clarifying structure 5) Rehearsing behavior occurred either verbal or written, though with few occurrences 6) Editing done by the subjects, though not occurring often, took the form of checks on syntax or lexicon, especially with word choice, while revisions like editing, though done less by the subjects, suggest that revising was a familiar writing strategy 7) The use of L1, though very limited, hastened the composing process in L2 8) The subjects considered purpose and audience--which partly characterized them as good writers 9) Concluding and submitting the essay was also done quite rapidly, which suggests that the subjects were glad the task was over and they were eager to leave. The study further concluded that: 1) The degree of recursiveness differs among ESL basic writers 2) The genre dictated by the topic or title, and the interest of the writer in the topic, determine the kind of composing strategy the basic ESL writers use and the frequency with which they employ certain composing dimensions: and 3) The use of L1 and consideration of audience and purpose facilitate ESL writers in their composing. The following generalizations can likewise be made: 1) Language Proficiency variable has a very low predictive validity for total composing and other writing strategies 2) Perceptions of Writing in the English language variable and Writing Experiences variable is not a reliable or effective predictor for total composing and other writing behavio